Undergraduate Education Students’ Perceptions of Effective and Ineffective Course Experiences: What Counts as an Effective Experience? - Aulls, Mark; Harley, Jason Matthew; Getahun, Dawit; Lemay, David (Alberta Journal of Educational Research, 2020)
Pre-service teachers’ conceptions of effective and ineffective instruction stand to inform their personal views of what constitutes effective and ineffective instruction, yet few qualitative studies have examined both conceptions of effective and ineffective instruction. The purpose of this study was to determine whether pre-service teachers described what happens in university courses primarily in terms of teacher characteristics, teaching practices, or instructional context. There were two research questions guiding the study. First, how are the dimensions of effective and ineffective instruction alike and different? Second, how do results correspond to similar qualitative studies? Nine distinct themes were inductively derived through open coding of 34 pre-service teachers’ essays: (a) motivation, (b) student autonomy, (c) meaningful learning, (d) comfortable learning environment, (e) classroom management, (f) student-teacher relationship, (g) teacher’s personal characteristics and manner, (h) lesson organization, and (i) teacher impact/student development. The results of this study support previous findings and add to the small number of studies that have examined pre-service teachers' descriptions of effective and ineffective instruction. Findings have also contributed a new category that has not appeared in previous literature: teacher impact/student development. Pre-service teachers’ descriptions in this study confirm that the theoretical conception of what happens in classrooms must include the teacher’s characteristics, teaching, and the context of instruction. Keywords: education theory and practice, educational psychology, higher education, teacher education, pre-service teacher beliefs, pre-service teacher conceptions, effective instruction, effective teaching. Les conceptions qu’ont les enseignants en formation de l’enseignement efficace et inefficace informent naturellement leurs points de vue personnels de ce qui constitue l’enseignement efficace et inefficace; pourtant, peu d’études qualitatives se sont penchées sur les conceptions de l’enseignement efficace ainsi que sur celles de l’enseignement inefficace. L’objectif de cette étude était de déterminer dans quelle mesure les enseignants en formation décrivent ce qui se passe dans les cours à l’université, notamment en fonction des caractéristiques des enseignants, des pratiques d’enseignement ou du contexte pédagogique. Deux questions ont guidé la recherche. D’abord, qu’est-ce que l’enseignement efficace et l’enseignement inefficace ont en commun et qu’est-ce qui les distingue? Deuxièmement, comment les résultats correspondent-ils à ceux d’études qualitatives similaires? Un codage ouvert de 34 dissertations écrites par des enseignants en formation a permis de recueillir, par induction, neuf thèmes distincts: (a) motivation, (b) autonomie des étudiants, (c) apprentissage significatif, (d) milieu d’apprentissage confortable, (e) gestion de la classe, (f) rapport étudiant-enseignant, (g) caractéristiques et manières personnelles de l’enseignant, (h) organisation des leçons, et (i) impact de l’enseignant/progression des étudiants. Les résultats de cette étude appuient ceux des études antérieures. Cette étude élargit le nombre restreint d’études qui ont porté sur les descriptions par des enseignants en formation de l’enseignement efficace et l’enseignement inefficace. Les résultats contribuent également à une nouvelle catégorie qui n’apparait pas dans les travaux antérieurs : impact de l’enseignant/progression des étudiants. Les descriptions par les enseignants en formation qui ont participé à cette étude confirment la conception théorique selon laquelle ce qui arrive dans la salle de classe doit tenir compte des caractéristiques personnelles de l’enseignant, de l’enseignement et du contexte pédagogique. Mots clés : théorie et pratique en éducation, psychologie de l’éducation; études supérieures, formation des enseignants; croyances des enseignants en formation, conceptions des enseignants en formation, enseignement efficace